The Role of the Academic Libraries in Promoting Awareness among Faculty Members - Saleem, Naifa Eid; Al-Suqri, Mohammed Nasser; Ali Al Kindi, Salim Said (Qualitative and Quantitative Methods in Libraries, 2019)
The current study aims to examine the reality of the role that the main library plays in promoting information awareness among faculty members of the College of Arts and Social Sciences (CASS). To achieve this goal, the study looked at the communication between the librarian at the Main Library and the faculty members of CASS. The study also looks at the way Main Library promotes awareness among the faculty members at CASS. In addition, the study attempts to identify difficulties that the Main Library faces in promoting awareness among CASS faculty members.